Manufacturing method of hydrogenated nitrile rubber
Patent Information
- Application Number
- JP2023140183
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0018】 本発明によれば、導電材分散液の粘度特性(分散性)や安定性に優れ、製造した電極のピール強度やサイクル試験後の活物質の割れを抑制し、且つ、電子化学素子の出力特性やサイクル特性を向上させうる水素化ニトリルゴムの製造方法が提供される。
Smart Images

Figure 2025034043000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing hydrogenated nitrile rubber, and more particularly to a method for producing hydrogenated nitrile rubber suitable for producing electrochemical elements. [Background technology]
[0002] Electrochemical devices such as lithium ion secondary batteries, lithium ion capacitors, and electric double layer capacitors are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are used in a wide range of applications. Therefore, in recent years, improvements in battery components such as electrodes have been studied in order to further improve the performance of electrochemical devices.
[0003] Here, an electrode used in an electrochemical element usually includes a current collector and an electrode mixture layer formed on the current collector. The electrode mixture layer is formed, for example, by applying a slurry containing an electrode active material and a binder composition containing a binding agent onto the current collector and drying the applied slurry.
[0004] In recent years, therefore, attempts have been made to improve the binder composition used in forming the electrode mixture layer in order to achieve further improvements in the performance of electrochemical elements. For example, a technique of using a polymer containing a nitrile group-containing monomer unit as a binding agent contained in the binder composition has been investigated.
[0005] For example, Patent Document 1 (JP 2018-160421 A) discloses a binder composition that contains a polymer containing a conjugated diene monomer unit and / or an alkylene structural unit and a nitrile group-containing monomer unit, and an organic solvent, and that has a solution turbidity of 1 to 80 at a solid content concentration of 10% by weight and has an excellent balance between peel strength and secondary battery output characteristics. Specifically, nitrile rubber latex, which is emulsion polymerized from acrylonitrile and 1,3-butadiene, is added to a 1% by weight calcium chloride aqueous solution to coagulate, then washed and filtered, and vacuum dried to obtain nitrile rubber. The obtained nitrile rubber is subjected to metathesis with a ruthenium-based Grubbs catalyst and ethylene as a coolefin, and then hydrogenated with a rhodium-based Wilkinson catalyst with an iodine value of 5 mg / 100 mg as the end point. Then, 0.2 parts of activated carbon with an average diameter of 15 μm is added and stirred for 30 minutes to obtain a hydrogenated polymer with a calcium ion concentration of 1000 ppm and an iodine value of 5 mg / 100 mg. Then, N-methylpyrrolidone (NMP) is added, and water is evaporated under reduced pressure to obtain an NMP solution of the hydrogenated polymer with a solution turbidity of 20. Electrodes are produced using a binder composition consisting of 1.6 parts of polyvinylidene fluoride (solution viscosity 5 kPa·s) and 0.4 parts of the hydrogenated polymer as the binder composition. However, the hydrogenated polymer produced here has a problem that the stability of the conductive material dispersion is poor, making it difficult to prepare electrochemical element electrodes. In addition, there has been a demand for improving the peel strength of the electrode and the effect of suppressing cracking of the electrode active material after cycle testing.
[0006] Patent Document 2 (Patent No. 6911985) discloses an electrochemical element having excellent rate characteristics and high-temperature storage stability, which includes a polymer containing an α,β-ethylenically unsaturated nitrile monomer unit and a specific alkylene structural unit, and having a volume average particle diameter D of 50 to 800 nm when dynamic light scattering measurement is performed, and at least one peak detected in the range of 5 μm to 30 μm, and a conductive carbon material. Specifically, acrylonitrile and 1,3-butadiene are copolymerized, dibutylhydroxytoluene (BHT) is added as an antiaging agent, and then a 25% by weight aqueous solution of calcium chloride is added in an amount of 3 parts per 100 parts of the polymer to coagulate, and 50 times the amount of ion-exchanged water is passed through to wash the polymer, and then a hydrogenation reaction is performed using a palladium catalyst, and the palladium catalyst is filtered off to obtain polymers with iodine values of 5 mg / 100 mg and 55 mg / 100 mg. The polymers are dissolved in NMP and used as a positive electrode binder. However, in the hydrogenated nitrile polymer produced here, it is desired to further improve the dispersibility of the dispersion liquid, the peel strength of the electrode, and the output characteristics, cycle characteristics, and effect of suppressing cracking of the electrode active material after cycle testing of the electrochemical element.
[0007] Patent Document 3 (WO2022 / 163769) discloses a non-aqueous secondary battery having excellent electrolyte mobility, which includes a positive electrode, a negative electrode, an electrolyte, and a separator, and in which a positive electrode composite layer containing a positive electrode active material, a conductive material, and a polymer A containing at least one of a nitrile group-containing monomer unit, a conjugated diene unit, and an alkylene structural unit is formed on a current collector. A specific example of polymer A is an emulsion polymerization solution obtained by emulsion polymerization of acrylonitrile and 1,3-butadiene, to which dibutylhydroxytoluene (BHT) is added, followed by addition of a 25% by weight aqueous calcium chloride solution to coagulate the solution, which is then hydrogenated using a palladium catalyst, and the palladium catalyst is filtered off to obtain a hydrogenated polymer with an iodine value of 20 mg / 100 mg. However, the hydrogenated polymer produced here has poor dispersibility in the conductive material dispersion, and there are problems such as output characteristics, cycle characteristics, and active material cracking after cycle testing of the electrochemical element produced.
[0008] On the other hand, Patent Document 4 (JP Patent Publication 2018-145434 A) discloses hydrogenated nitrile rubber containing a substituted phenol useful for sealing materials, hose materials, transmission hoses, etc. in the automotive field. Specifically, 4-methyl-2,6-tert-butylphenol (BHT) is added to a polymerization liquid obtained by emulsion polymerization of acrylonitrile and 1,3-butadiene, and the mixture is coagulated with an aqueous sodium chloride solution or an aqueous magnesium chloride solution prepared with calcium ion-containing tap water. The mixture is then washed with calcium ion-containing tap water to obtain NBR having a calcium content of 285 to 595 ppm. Next, the mixture is hydrogenated to a hydrogenation level of 99.4 ± 0.2% in a chlorobenzene solution using a rhodium-based catalyst, and the polymer liquid is diluted to remove rhodium. After that, a carboxyl group-containing water-soluble polymer, a 2% aqueous calcium chloride solution (0.15 parts by weight based on 100 parts by weight of hydrogenated nitrile rubber), and a dilute aqueous sodium hydroxide solution are continuously measured and coagulated to obtain hydrogenated nitrile rubber. However, even if the hydrogenated nitrile rubber produced here is used for producing an electrode, the peel strength of the produced electrode and the output characteristics and cycle characteristics of the electrochemical element are inferior, and furthermore, cracks occur in the electrode active material after cycle testing, making it unsuitable as a binder for producing electrodes. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2018-160421 A [Patent Document 2] Patent No. 6911985 [Patent Document 3] WO2022 / 163769 publication [Patent Document 4] JP 2018-145434 A Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been made in consideration of the above circumstances, and has an object to provide a method for producing hydrogenated nitrile rubber which, when used to produce an electrode for an electrochemical element, provides an excellent viscosity characteristic (dispersibility) and stability of a conductive material dispersion, and which provides an excellent peel strength of the resulting electrode and excellent suppression of cracking of the active material in the electrode after a cycle test, and which also provides excellent output characteristics and cycle characteristics of the electrochemical element. [Means for solving the problem]
[0011] The present inventors have conducted intensive research in view of the above problems, and have found that hydrogenated nitrile rubber obtained by emulsion polymerizing a monomer component containing a nitrile group-containing monomer and a conjugated diene monomer, adding a phenol-based antioxidant, coagulating the isolated polymer with calcium chloride, and hydrogenating the polymer with a rhodium-based catalyst and / or a ruthenium-based catalyst when used as a positive electrode binder for an electrochemical element has excellent viscosity characteristics and stability of the dispersion liquid, and therefore improves the peel strength of the produced electrode and suppresses cracking of the electrode active material after a cycle test, and further enhances the output characteristics and cycle characteristics of the electrochemical element.
[0012] The present inventors have also confirmed that the hydrogenated nitrile rubber produced has an iodine value in a specific range, and contains a specific antioxidant. The inventors have also found that the above-mentioned properties can be further improved by using only those hydrogenated nitrile rubbers having a limited amount of metal as a positive electrode binder.
[0013] Based on these findings, the present inventors have completed the present invention.
[0014] Thus, according to the present invention, there is provided a method for producing hydrogenated nitrile rubber, which comprises emulsion polymerizing a monomer component containing a nitrile group-containing monomer and a conjugated diene monomer, adding a phenol-based antioxidant, coagulating the polymer with calcium chloride, and hydrogenating the polymer with a rhodium-based catalyst and / or a ruthenium-based catalyst.
[0015] In the method for producing hydrogenated nitrile rubber of the present invention, it is preferable to provide a purification step of the hydrogenated nitrile rubber after the hydrogenation.
[0016] In the method for producing hydrogenated nitrile rubber of the present invention, it is preferable that the hydrogenated nitrile rubber contains a phenol-based antioxidant, has an iodine value of 150 mg / 100 mg or less, a calcium (Ca) amount of 4000 ppm or less, a rhodium (Rh) and / or ruthenium (Ru) content of 50 ppm or less, a sodium (Na) content of 300 ppm or less, a magnesium (Mg) content of 50 ppm or less, and a palladium (Pd) content of 50 ppm or less.
[0017] In the method for producing hydrogenated nitrile rubber of the present invention, the hydrogenated nitrile rubber is preferably used as a positive electrode binder for an electrochemical element. Effect of the Invention
[0018] According to the present invention, there is provided a method for producing hydrogenated nitrile rubber which provides a conductive material dispersion excellent in viscosity characteristics (dispersibility) and stability, suppresses the peel strength of the produced electrode and cracking of the active material after a cycle test, and can improve the output characteristics and cycle characteristics of an electrochemical device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, an embodiment of the present invention will be described in detail.
[0020] The method for producing hydrogenated nitrile rubber of the present invention is characterized in that a monomer component containing a nitrile group-containing monomer and a conjugated diene monomer is emulsion-polymerized, a phenol-based antioxidant is added, and then the polymer obtained by coagulating the polymer with calcium chloride is hydrogenated using a rhodium-based catalyst and / or a ruthenium-based catalyst.
[0021] <Monomer components> (Nitrile group-containing monomer) The nitrile group-containing monomer to be used may be an α,β-ethylenically unsaturated nitrile monomer. Specifically, the α,β-ethylenically unsaturated nitrile monomer is not particularly limited as long as it is an α,β-ethylenically unsaturated compound having a nitrile group, and may be, for example, acrylonitrile; α-halogenoacrylonitrile such as α-chloroacrylonitrile and α-bromoacrylonitrile; α-alkylacrylonitrile such as methacrylonitrile and α-ethylacrylonitrile; and the like, and is preferably acrylonitrile. These nitrile group-containing monomers may be used alone or in combination of two or more, and the proportion of each monomer used is preferably 10% by weight or more, more preferably 15% by weight or more, and even more preferably 20% by weight or more, and preferably 50% by weight or less, more preferably 45% by weight or less, and even more preferably 40% by weight or less, based on the total monomer components. If the content of the nitrile group-containing monomer is within the above-mentioned range, the dispersion stability of the conductive material dispersion can be increased, and the peel strength of the obtained electrode can be further improved.
[0022] (Conjugated diene monomer) Examples of the conjugated diene monomer to be used include conjugated diene compounds having 4 or more carbon atoms, such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, etc. Among these, isoprene and 1,3-butadiene are preferred, and 1,3-butadiene is particularly preferred.
[0023] These conjugated dienes can be used alone or in combination of two or more, and the proportion of them used is preferably 50% by weight or more, more preferably 55% by weight or more, and particularly preferably 60% by weight or more, and preferably 90% by weight or less, more preferably 85% by weight or less, and particularly preferably 80% by weight or less, based on the total monomer components. If the proportion of the conjugated diene monomer in the polymerization components is within the above range, the dispersion stability of the conductive material dispersion and the cycle characteristics of the electrochemical device can be improved.
[0024] (Other monomer components) In the present invention, in addition to the above-mentioned nitrile group-containing monomer and conjugated diene, other monomer components may be used as necessary. For example, aromatic vinyl monomer units, acidic group-containing monomer units, and (meth)acrylic acid ester monomer units may be mentioned.
[0025] Examples of aromatic vinyl monomers capable of forming the aromatic vinyl monomer unit include styrene, α-methylstyrene, pt-butylstyrene, butoxystyrene, vinyltoluene, chlorostyrene, and vinylnaphthalene.
[0026] Examples of the acidic group-containing monomer capable of forming the acidic group-containing monomer unit include a carboxylic acid group-containing monomer, a sulfonic acid group-containing monomer, and a phosphoric acid group-containing monomer. The acidic group-containing monomer may be used alone or in any combination of two or more kinds at any ratio.
[0027] Examples of the carboxylic acid group-containing monomer include monocarboxylic acids and their derivatives, dicarboxylic acids and their acid anhydrides, and their derivatives.
[0028] Examples of the monocarboxylic acid include acrylic acid, methacrylic acid, and crotonic acid.
[0029] Examples of the monocarboxylic acid derivatives include 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, and α-chloro-β-E-methoxyacrylic acid.
[0030] The dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid.
[0031] Examples of dicarboxylic acid derivatives include methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, and maleic acid monoesters such as nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate.
[0032] Examples of the acid anhydrides of dicarboxylic acids include maleic anhydride, acrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride.
[0033] Furthermore, as the carboxylic acid group-containing monomer, an acid anhydride that generates a carboxylic acid group by hydrolysis can also be used. Among them, acrylic acid and methacrylic acid are preferred as the carboxylic acid group-containing monomer.
[0034] Examples of the sulfonic acid group-containing monomer include vinyl sulfonic acid, methyl vinyl sulfonic acid, (meth)allyl sulfonic acid, styrene sulfonic acid, (meth)acrylic acid-2-ethyl sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid. In the present invention, "(meth)allyl" means allyl and / or methallyl.
[0035] Examples of the phosphate group-containing monomer include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate. In the present invention, "(meth)acryloyl" means acryloyl and / or methacryloyl.
[0036] Examples of (meth)acrylic acid ester monomers capable of forming a (meth)acrylic acid ester monomer unit include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, and stearyl acrylate. Acrylic acid alkyl esters: methacrylic acid alkyl esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, and stearyl methacrylate.
[0037] These other monomers can be used alone or in combination of two or more kinds, and the amount used is appropriately selected within a range that does not impair the object of the present invention, and is usually preferably 30% by weight or less, more preferably 20% by weight or less, even more preferably 10% by weight or less, and particularly preferably 5% by weight or less.
[0038] (Emulsion polymerization method) The emulsion polymerization of the monomer components may be carried out in accordance with a conventional method, for example, by emulsifying the monomers with water using an emulsifier and then using a polymerization catalyst.
[0039] The emulsifier used in the emulsion polymerization is not particularly limited, but examples thereof include anionic emulsifiers, cationic emulsifiers, and nonionic emulsifiers, with anionic emulsifiers being preferred.
[0040] The anionic emulsifier is not particularly limited, and examples thereof include salts of fatty acids such as myristic acid, palmitic acid, oleic acid, and linolenic acid; alkylbenzenesulfonates such as sodium dodecylbenzenesulfonate; sulfates such as sodium lauryl sulfate, and phosphates such as polyoxyalkylene alkyl ether phosphates; and alkylsulfosuccinates. Among these anionic emulsifiers, fatty acid salts and sulfates are preferred, and fatty acid salts are particularly preferred. Suitable sulfates include, for example, sodium lauryl sulfate, ammonium lauryl sulfate, sodium myristyl sulfate, sodium laureth sulfate, sodium polyoxyethylene alkyl sulfate, and sodium polyoxyethylene alkylaryl sulfate. Suitable fatty acid salts include, for example, potassium oleate, sodium oleate, and potassium palmitate, and potassium oleate is particularly preferred.
[0041] These emulsifiers can be used alone or in combination of two or more. The amount used is usually 0.01 to 10 parts by weight, preferably 0.1 to 5 parts by weight, and more preferably 1 to 3 parts by weight, per 100 parts by weight of the monomer component.
[0042] The monomer component, emulsifier, and water may be mixed in a conventional manner, such as by stirring the monomer, emulsifier, and water with a stirrer such as a homogenizer or a disk turbine. The amount of water used is usually 10 to 750 parts by weight, preferably 50 to 500 parts by weight, and more preferably 100 to 400 parts by weight, based on 100 parts by weight of the monomer component.
[0043] The polymerization catalyst used in the emulsion polymerization is not particularly limited as long as it is one that is usually used in emulsion polymerization, and for example, a radical generator can be used. If necessary, a redox catalyst can be used in combination with a reducing agent.
[0044] Examples of the radical generator include peroxides and azo compounds, and preferably peroxides. As the peroxide, inorganic peroxides and organic peroxides can be used. Examples of inorganic peroxides include sodium persulfate, potassium persulfate, hydrogen peroxide, and ammonium persulfate. Among these, potassium persulfate, hydrogen peroxide, and ammonium persulfate are preferred, and potassium persulfate is particularly preferred.
[0045] There are no particular limitations on the organic peroxide, so long as it is a known peroxide used in emulsion polymerization. Examples of the organic peroxide include diisopropylbenzene hydroperoxide, cumene hydroperoxide, paramenthane hydroperoxide, and benzoyl peroxide.
[0046] These radical generators can be used alone or in combination of two or more kinds. The amount of the radical generator used is usually in the range of 0.0001 to 5 parts by weight, preferably 0.0005 to 1 part by weight, and more preferably 0.001 to 0.5 parts by weight, per 100 parts by weight of the monomer component.
[0047] The emulsion polymerization reaction may be carried out according to a conventional method, and may be any of batch, semi-batch, and continuous. The polymerization temperature and polymerization time are not particularly limited and may be appropriately selected depending on the type of polymerization initiator used. The polymerization temperature is usually in the range of 0 to 100°C, preferably 5 to 80°C, and more preferably 10 to 50°C, and the polymerization time is usually 0.5 to 100 hours, and preferably 1 to 10 hours.
[0048] (Anti-aging agent addition process) The present invention is characterized in that a phenolic antioxidant is added to the emulsion polymerization liquid obtained by the emulsion polymerization. The effect of the phenolic antioxidant is much higher and more preferable when the phenolic antioxidant is added to the emulsion polymerization liquid obtained by emulsion polymerization of the monomer and uniformly dispersed in the emulsion polymerization liquid to produce a hydrogenated nitrile rubber than when it is mixed with the hydrogenated nitrile rubber after production. Although it is not possible to measure this, it is believed that the phenolic antioxidant is uniformly and finely dispersed in the hydrogenated nitrile rubber obtained as it is by coagulating the emulsion polymerization liquid in which the phenolic antioxidant is uniformly dispersed with calcium chloride, which will be described later, and thus exhibiting a high effect.
[0049] The phenol-based antioxidant to be used is not particularly limited as long as it is a commonly used one, but a hindered phenol-based antioxidant is particularly preferred because it highly stabilizes the conductive material dispersion. In the present invention, the hindered phenol-based antioxidant refers to a phenol-based antioxidant having bulky substituents on both sides of the phenol group, and the bulky substituents on both sides are an isobutyl group or a t-butyl group, preferably a t-butyl group.
[0050] Examples of the hindered phenol-based antioxidants include 2,6-di-t-butylphenol, 2,6-di-t-butyl-4-methylphenol, 2,6-di-t-butyl-α-dimethylamino-p-cresol, 3-(4-hydroxy-3,5-di-t-butylphenyl)butyl propionate, 3-(4-hydroxy-3,5-di-t-butylphenyl)hexyl propionate, 3-(4-hydroxy-3,5-di-t-butylphenyl)octyl propionate, 3-(4-hydroxy-3,5-di-t-butylphenyl)decyl propionate, 3-(4-hydroxy-3,5-di-t-butylphenyl)dodecyl propionate, 3-(4-hydroxy-3,5-di-t-butylphenyl)isopropyl ... 3-(4-hydroxy-3,5-diisopropylphenyl)propionate, octadecyl 3-(4-hydroxy-3,5-diisopropylphenyl)propionate, heptyl 3-(4-hydroxy-3,5-diisopropylphenyl)propionate, octyl 3-(4-hydroxy-3,5-diisopropylphenyl)propionate, dodecyl 3-(4-hydroxy-3,5-diisopropylphenyl)propionate, octadecyl 3-(4-hydroxy-3,5-diisopropylphenyl)propionate, 4,4'-methylenebis(2,6-dibutylphenol), 2,6-di-t-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, and the like are included, and 2,6-di-t-butyl-4-methylphenol (dibutylhydroxytoluene = BHT) is preferred.
[0051] The method of adding the phenol-based antioxidant to the emulsion polymerization liquid is not particularly limited, and may be any conventional method.
[0052] The amount of the phenol-based antiaging agent used may be appropriately selected so as to be the content of the antiaging agent in the hydrogenated nitrile rubber of the present invention, and is usually in the range of 0.001 to 15 parts by weight, preferably 0.01 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, particularly preferably 0.3 to 3 parts by weight, and most preferably 0.5 to 2 parts by weight, relative to 100 parts by weight of the monomer component.
[0053] (solidification process) The present invention is characterized in that the emulsion polymerization liquid to which the phenol-based antioxidant has been added is coagulated with calcium chloride. In particular, coagulation with calcium chloride is preferable because the coagulation activity of the emulsion polymerization liquid is high, only a small amount of calcium chloride is added, and it is easy to remove from the polymer by washing with water or activated carbon treatment in a subsequent process. Therefore, the calcium (Ca) content in the hydrogenated nitrile rubber produced can be controlled. In the production of an electrochemical element, the hydrogenated nitrile rubber having a Ca content within a specific range is preferably used to increase the dispersibility of the conductive material dispersion liquid, thereby increasing the peel strength of the electrode and suppressing cracking of the electrode active material after cycle characteristics.
[0054] The calcium chloride used is usually used as an aqueous calcium chloride solution, and the coagulant concentration is usually in the range of 0.1 to 70% by weight, preferably 1 to 60% by weight, more preferably 5 to 50% by weight, and particularly preferably 10 to 30% by weight, which is suitable for concentrating the particle size of the generated hydrous crumbs uniformly in a specific region.
[0055] The temperature of the coagulation liquid is not particularly limited, but when it is usually 40°C or higher, preferably 40 to 90°C, more preferably in the range of 50 to 80°C, uniform water-containing crumbs are preferably formed.
[0056] After the coagulation reaction, the coagulated product is washed with water and then dried to obtain a polymer to be hydrogenated.
[0057] (Hydrogenation process) The present invention is characterized in that the polymer obtained above is subjected to a hydrogenation reaction using a rhodium-based catalyst and / or a ruthenium-based catalyst.
[0058] The hydrogenation reaction using a rhodium-based catalyst and / or a ruthenium-based catalyst may be carried out according to a conventional method, for example, the method described in Japanese Patent No. 4509792. Here, an example of the hydrogenation reaction using Grubbs catalyst as the ruthenium-based catalyst and Wilkinson catalyst as the rhodium-based catalyst is given.
[0059] Hydrogenation reactions using Grubbs catalyst The Grubbs catalyst to be used is not particularly limited, but suitable examples include bis(tricyclohexylphosphine)benzylidene ruthenium dichloride, 1,3-bis(2,4,6-trimethylphenyl)-2-(imidazolidinylidene)(dichlorophenylmethylene)(tricyclohexylphosphine)ruthenium, and the like.
[0060] Grubbs catalysts have the property of metathesis of hydrogenated nitrile rubber when used with coolefins, and are used to adjust the molecular weight of hydrogenated nitrile rubber. In the presence of hydrogen, Grubbs catalysts are converted into the dihydride complex (PR3)2RuCl2H2, which is an olefin hydrogenation catalyst. Therefore, in reactions using Grubbs catalysts, a metathesis reaction is first carried out using coolefins, and then hydrogen is introduced to carry out the hydrogenation reaction.
[0061] Examples of the coolefin to be used include olefins having 2 to 16 carbon atoms, such as ethylene, isobutane, styrene, and 1-hexane; and functional group-containing unsaturated compounds, such as cis-2-butene-1,4-diol, 3-butene-1-amine, vinyltrimethoxysilane, methoxypolyalkylene glycol methacrylate, and 2-(methacryloyloxy)ethanesulfonic acid. Of these, functional group-containing unsaturated compounds are preferred.
[0062] The amount of the coolefin used is usually in the range of 0.1 to 20 parts by weight, preferably 0.5 to 10 parts by weight, and more preferably 1 to 5 parts by weight, based on 100 parts by weight of the polymer.
[0063] The reaction can be carried out in any solvent that does not inactivate the catalyst or interfere with the reaction. Preferred solvents include, but are not limited to, dichloromethane, benzene, toluene, tetrahydrofuran, cyclohexane, monochlorobenzene (MCB), and the like, most preferably MCB. In some cases, the coolefin itself can act as the solvent, in which case no other solvent is required.
[0064] The temperature of the metathesis reaction is usually in the range of 20 to 140° C., preferably 60 to 120° C. The reaction time depends on many factors such as the cement concentration, the amount of catalyst used, and the reaction temperature, but is usually complete within 2 hours. The progress of the metathesis reaction can be monitored using standard analytical methods, such as GPC or solution viscosity.
[0065] The hydrogenation reaction can be carried out by filling the reaction vessel with hydrogen after the above metathesis. The pressure of the hydrogenation reaction is not particularly limited, but is usually in the range of 0.1 to 30 MPa, preferably 1 to 20 MPa.
[0066] In addition, it is possible to carry out only the hydrogenation reaction by filling the reactor with hydrogen from the beginning without using a co-olefin.
[0067] Wilkinson's Catalyst for Hydrogenation The hydrogenation reaction using Wilkinson's catalyst ((PPh3)3RhCl) is advantageous because it can be carried out in the same reaction vessel after the metathesis reaction using Grubbs' catalyst by adding the hydrogenation catalyst to the vessel without isolating the metathesis product.
[0068] Examples of the solvent for the hydrogenation reaction include acetone, methyl ethyl ketone, ethyl acetate, tetrahydrofuran, 1,3-dioxane, benzene, toluene, methylene chloride, chloroform, monochlorobenzene (MCB), dichlorobenzene, etc. Among these, MCB is particularly suitable as a good solvent for both the nitrile group-containing nitrile rubber before hydrogenation and the hydrogenated nitrile rubber after hydrogenation.
[0069] The amount of the hydrogenation catalyst used may be appropriately selected depending on the purpose of use and the iodine value, but is usually in the range of 0.001 to 0.5 parts by weight, preferably 0.005 to 0.1 parts by weight, or 0.01 to 0.05 parts by weight based on 100 parts by weight of the polymer before hydrogenation.
[0070] In the hydrogenation reaction, a cocatalyst can be used as necessary. Examples of the cocatalyst include phosphine, diphosphine, triphenylphosphine, etc., and preferably triphenylphosphine. The amount of these cocatalysts used is usually in the range of 0.01 to 15% by weight, preferably 0.1 to 10 parts by weight, more preferably 0.5 to 5% by weight, based on 100 parts by weight of the polymer to be hydrogenated.
[0071] The pressure for the hydrogenation reaction is not particularly limited, but is usually in the range of 0.1 to 30 MPa, preferably 1 to 20 MPa, and more preferably 5 to 15 MPa.
[0072] The hydrogenation reaction temperature is usually in the range of 30 to 200° C., preferably 50 to 170° C., and more preferably 100 to 150° C. The reaction time is usually 1 to 50 hours, and preferably 2 to 25 hours.
[0073] The hydrogenation reaction can be stopped once the desired hydrogenation level has been reached by depressurizing the reactor or by cooling it. Residual hydrogen is usually removed by a nitrogen purge. The hydrogenation catalyst can also be removed prior to removal of the solvent and isolation of the hydrogenated nitrile rubber from the organic layer.
[0074] After the hydrogenation reaction, the solvent is removed and the product is dried to obtain hydrogenated nitrile rubber.
[0075] <Hydrogenated nitrile rubber> The hydrogenated nitrile rubber thus obtained is not particularly limited, but is suitable for producing an electrochemical element if it contains a phenol-based antioxidant, has an iodine value of 150 mg / 100 mg or less, a calcium (Ca) amount of 4000 ppm or less, a rhodium (Rh) and / or ruthenium (Ru) content of 50 ppm or less, a sodium (Na) content of 300 ppm or less, a magnesium (Mg) content of 50 ppm or less, and a palladium (Pd) content of 50 ppm or less.
[0076] The repeating units of the hydrogenated nitrile rubber produced can be used without any problem so long as they are within the range produced by using the above-mentioned monomer components in the proportions used.
[0077] The content of the phenol-based antioxidant in the produced hydrogenated nitrile rubber is not particularly limited, but is usually in the range of 0.001 to 2% by weight, preferably 0.01 to 1% by weight, and more preferably 0.1 to 0.5% by weight.
[0078] The iodine value of the hydrogenated nitrile rubber produced is not particularly limited, but is usually 150 mg / 100 mg or less, preferably 120 mg / 100 mg or less, more preferably 100 mg / 100 mg or less, and particularly preferably 80 mg / 100 mg or less. If the iodine value of the hydrogenated nitrile rubber is within this range, the element characteristics (such as cycle characteristics) of the electrochemical element can be improved. If the iodine value of the hydrogenated nitrile rubber is equal to or greater than the lower limit, the peel strength of the electrochemical element electrode can be improved.
[0079] The weight average molecular weight (Mw) of the hydrogenated nitrile rubber produced is not particularly limited, but is usually in the range of 1,000 to 1,000,000, preferably 2,000 to 500,000, more preferably 4,000 to 400,000, and most preferably 5,000 to 250,000. If the weight average molecular weight (Mw) of the hydrogenated nitrile rubber is in this range, the dispersion stability of the conductive material dispersion can be increased, and the peel strength of the obtained electrode can be increased, which is preferable.
[0080] The calcium (Ca) content in the hydrogenated nitrile rubber produced is not particularly limited, but is usually 4000 ppm or less, preferably 1 to 2500 ppm, more preferably 10 to 2000 ppm, more preferably 30 to 1500 ppm, and most preferably in the range of 50 to 800 ppm. When the Ca content in the hydrogenated nitrile rubber is in this range, cracking of the electrode active material in the obtained electrode can be suppressed well, and the peel strength of the electrode can be increased. In addition, when the Ca content in the hydrogenated nitrile rubber is in this range, the dispersion stability of the conductive material can be increased when a conductive material dispersion liquid is prepared, and the cycle characteristics of the obtained electrochemical element can be improved, which is preferable.
[0081] The rhodium (Rh) and / or ruthenium (Ru) content (total amount of Ru+Rh) in the produced hydrogenated nitrile rubber is not particularly limited, but is usually 50 ppm or less, preferably 30 ppm or less, and more preferably 20 ppm or less, which is suitable in that cracking of the active material in the produced electrode can be suppressed.
[0082] The sodium (Na) content in the hydrogenated nitrile rubber of the present invention is 300 ppm or less, preferably 200 ppm or less, more preferably 100 ppm or less, and most preferably 50 ppm or less. When the Na content in the hydrogenated nitrile rubber is in this range, cracking of the active material in the electrode is suppressed, and the cycle characteristics of the electrochemical element are improved, which is preferable.
[0083] The palladium (Pd) content in the hydrogenated nitrile rubber of the present invention is not particularly limited, but is usually 50 ppm or less, preferably 30 ppm or less, more preferably 10 ppm or less, and most preferably 5 ppm or less. When the Pd content in the hydrogenated nitrile rubber is in this range, cracking of the active material in the electrode is suppressed, and the cycle characteristics of the electrochemical element are improved, which is preferable.
[0084] The magnesium (Mg) content in the hydrogenated nitrile rubber of the present invention is not particularly limited, but is usually 50 ppm or less, preferably 40 ppm or less, more preferably 30 ppm or less, and most preferably 20 ppm or less. When the Mg content in the nitrile polymer is in this range, cracking of the active material in the electrode is suppressed, and the cycle characteristics of the electrochemical element are improved, which is preferable. EXAMPLES
[0085] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the following description, the units "%", "ppm" and "parts" that represent amounts are by weight unless otherwise specified.
[0086] In a polymer produced by copolymerizing a plurality of types of monomers, the ratio of a monomer unit formed by polymerizing a certain monomer in the polymer usually coincides with the ratio (feed ratio) of the certain monomer in all monomers used in the polymerization of the polymer, unless otherwise specified. In addition, when a polymer is a hydrogenated polymer obtained by hydrogenating a polymer containing a conjugated diene monomer unit, the total content ratio of unhydrogenated conjugated diene monomer units and alkylene structural units as hydrogenated conjugated diene monomer units in the hydrogenated polymer coincides with the ratio (feed ratio) of the conjugated diene monomer in all monomers used in the polymerization of the polymer.
[0087] In the examples and comparative examples, various measurements and evaluations were carried out according to the following methods.
[0088] <Iodine value> The iodine value of the hydrogenated nitrile rubber was measured in accordance with JIS K 6235.
[0089] <Weight average molecular weight> The weight average molecular weight (Mw) of the hydrogenated nitrile rubber was measured by gel permeation chromatography (GPC) under the following measurement conditions using a 10 mM LiBr-dimethylformamide (DMF) solution. Separation column: Shodex KD-806M (Showa Denko K.K.) Detector: Differential refractometer detector RID-10A (Shimadzu Corporation) Eluent flow rate: 0.3mL / min Column temperature: 40℃ Standard polymer: TSK standard polystyrene (manufactured by Tosoh Corporation)
[0090] <Metal content> Approximately 0.5 g of hydrogenated nitrile rubber was collected in terms of solid content, dissolved in approximately 5 mL of concentrated sulfuric acid, carbonized on a heater, and then incinerated in an electric furnace at 1000 ° C for approximately 3 hours. After cooling, approximately 2 mL of concentrated nitric acid was gradually added to perform wet decomposition. After decomposition, the acid was concentrated and the volume was adjusted to 10 mL with ultrapure water, and the metal ion concentration was measured using ICP-MS (Agilent, ICP-MS 7900). The metal ion concentration contained in the hydrogenated nitrile rubber was calculated from the measured value. At this time, the metal ions measured were calcium ions, rhodium ions, ruthenium ions, palladium ions, iron ions, sodium ions, and magnesium ions.
[0091] <Viscosity of conductive material dispersion> The viscosity of the conductive material dispersion obtained in each of the Examples and Comparative Examples was measured using a rheometer ("MCR302" manufactured by Anton Paar) at a temperature of 25°C and a shear rate of 10 (1 / s) for 120 seconds, and the average viscosity measurement value from 61 seconds to 120 seconds was evaluated according to the following criteria. A: 1Pa·s or less B: More than 1Pa·s and less than 5Pa·s C: More than 5Pa·s and less than 10Pa·s D: More than 10Pa·s
[0092] <Stability of conductive material dispersion> The conductive material dispersion obtained in each Example and Comparative Example was measured for viscosity (η0) and then stored in a sealed container at 25°C for 10 days. The dispersion viscosity was then measured again (η1) and the viscosity change rate was calculated according to the following formula, which was used as the conductive material dispersion stability. Evaluation was performed according to the following criteria. Viscosity change rate Δη=η1 / η0×100 A: Viscosity change rate Δη is 90% or more and 110% or less B: Viscosity change rate Δη is 80% or more and less than 90% C: Viscosity change rate Δη is 70% or more and less than 80% D: Viscosity change rate Δη is less than 70% or more than 110%
[0093] <Peel strength> The positive electrodes prepared in the examples and comparative examples were cut into a rectangle of length: 100 mm, width: 10 mm to prepare test pieces, and cellophane tape (compliant with JIS Z1522) was attached to the surface of the positive electrode composite layer with the surface having the positive electrode composite layer facing down, and the stress when one end of the current collector was pulled vertically at a pulling speed of 100 mm / min and peeled off was measured (note that the cellophane tape was fixed to the test table). The measurement was performed three times, and the average value was calculated, which was taken as the peel strength and evaluated according to the following criteria. The larger the peel strength value, the stronger the adhesion of the positive electrode composite layer to the current collector made of aluminum foil. A: Peel strength is 15N / m or more B: Peel strength is 10N / m or more and less than 15N / m C: Peel strength is 5N / m or more and less than 10N / m D: Peel strength is less than 5N / m
[0094] <Cycle characteristics> The lithium ion secondary batteries prepared in the examples and comparative examples were left to stand at 25°C for 5 hours after injecting the electrolyte. Next, they were charged to a cell voltage of 3.65V at 25°C and 0.2C by a constant current method, and then aged at 60°C for 12 hours. Then, they were discharged to a cell voltage of 3.00V at 25°C and 0.2C by a constant current method. Then, they were CC-CV charged (upper cell voltage 4.20V) at 0.2C by a constant current method, and CC discharged to 3.00V by a constant current method of 0.2C. This charge and discharge at 0.2C was repeated three times. Next, 300 cycles of charge and discharge were performed at a cell voltage of 4.20-3.00V and a charge and discharge rate of 1.0C in an environment of 45°C. The discharge capacity of the first cycle was defined as X1, and the discharge capacity of the 300th cycle was defined as X2. Using the discharge capacity X1 and the discharge capacity X2, the capacity retention rate = (X2 / X1) x 100 (%) was calculated and evaluated according to the following criteria. A higher value of the capacity retention rate indicates that the lithium ion secondary battery has better cycle characteristics. A: Capacity retention rate is 85% or more B: Capacity retention rate is 80% or more but less than 85% C: Capacity retention rate is 75% or more but less than 80% D: Capacity retention rate is less than 75%
[0095] <Whether or not the active material cracks after cycling> The lithium ion secondary batteries produced in the Examples and Comparative Examples were disassembled after the cycle test, and the cross-sectional SEM images of the removed positive electrodes were observed at 1000x magnification. The number of cracks observed in the active material was evaluated as follows. A: Less than 2 pieces of broken active material B: The number of broken active materials is 2 or more but less than 5 C: The number of broken active materials is 5 or more but less than 9 D: The number of broken active materials is 9 or more.
[0096] <Output characteristics> The output characteristics of the lithium ion secondary batteries produced in the Examples and Comparative Examples were evaluated by measuring the IV resistance by the following method. As in the case of the cycle characteristics, the lithium-ion secondary battery was subjected to aging treatment and three repeated charge / discharge cycles, and then charged at 25°C until the charge rate reached 50% (i.e., until the charge capacity reached 350mAh for a cell capacity of 700mAh), and the resistance value was measured using the following procedure. (1) Calculate the voltage change ΔV(0.2) when discharging for 30 seconds using a 0.2C constant current method (I0.2). (2) Charge using the 0.2C constant current method for 30 seconds. (3) Calculate the voltage change ΔV(1.0) when discharging for 30 seconds using a 1.0C constant current method (I1.0). IV resistance value (Ω)={ΔV(1.0)-ΔV(0.2)} / (I1.0-I0.2) According to the calculated IV resistance value, the evaluation was performed as follows. A: 0.25Ω or less B: More than 0.25Ω and less than 0.30Ω C: More than 0.30Ω and less than 0.35 D: More than 0.35Ω
[0097] Example 1 <Production of hydrogenated nitrile rubber> -Emulsion polymerization process- Into a reactor having an internal volume of 10 L, 100 parts of ion-exchanged water, 33 parts of acrylonitrile as an α,β-ethylenically unsaturated nitrile monomer, and 67 parts of 1,3-butadiene as a conjugated diene monomer were charged, and 2 parts of potassium oleate as an emulsifier, 0.1 parts of potassium phosphate as a stabilizer, and further, 0.3 parts of tert-dodecyl mercaptan (TDM) as a molecular weight regulator were added, and emulsion polymerization was carried out at a temperature of 5°C in the presence of 0.35 parts of potassium persulfate as a polymerization initiator, thereby copolymerizing acrylonitrile and 1,3-butadiene.
[0098] -Anti-aging additive process- When the polymerization conversion rate reached 89%, 0.2 parts of hydroxylamine sulfate per 100 parts of monomer was added to terminate the polymerization. The mixture was then heated and steam distilled at about 90°C under reduced pressure to recover the residual monomer, and 0.1 parts of dibutylhydroxytoluene (BHT), a phenolic antioxidant, was added to obtain an emulsion polymerization liquid.
[0099] A 25% aqueous solution of calcium chloride (CaCl2) was added as a coagulant in an amount of 3 parts per 100 parts of polymer solids in the obtained emulsion polymerization liquid while stirring, and the polymer in the emulsion polymerization liquid was coagulated. After that, the polymer was filtered, washed with 50 times the amount of ion-exchanged water relative to the obtained polymer, and then dried under reduced pressure at a temperature of 90°C to obtain a polymer.
[0100] -Hydrogenation process I (metase reaction)- Next, 9 parts of the obtained polymer was dissolved in 141 parts of monochlorobenzene, which is a halogenated hydrocarbon, and the solution was put into a reactor. Then, after heating the reactor to 80°C, 2 L of a monochlorobenzene solution containing bis(tricyclohexylphosphine)benzylidene ruthenium dichloride as a Grubbs catalyst was added so that the amount of Grubbs catalyst relative to the polymer was 1000 ppm. Then, 4.4 parts of cis-2-butene-1,4-diol as a coolefin was added relative to 100 parts of precursor 1, and the polymer was subjected to a metathesis reaction at a stirring speed of 600 rpm. During the reaction, the temperature was kept constant using a cooling coil connected to a temperature control device and a heat sensor.
[0101] -Hydrogenation process II (hydrogenation reaction)- Then, the inside of the reactor was degassed three times with 0.7 MPa H2 while continuing stirring. Then, the temperature of the reactor was raised to 130°C, and 1 L of a monochlorobenzene solution containing Wilkinson's catalyst and triphenylphosphine was added to the reactor. The amount of Wilkinson's catalyst was 0.03 parts and the amount of triphenylphosphine was 1 part per 100 parts of the polymer. Then, the temperature was raised to 138°C, and the hydrogenation reaction of the polymer was carried out under the condition of a hydrogen pressure (gauge pressure) of 8.4 MPa.
[0102] -Purification process- After the hydrogenation reaction was completed, 0.2 parts of activated carbon with an average diameter of 15 μm was added to the reactor and stirred for 30 minutes to adjust the concentration of divalent or higher metal ions including calcium ions. The mixture was then filtered through a filter with a pore size of 5 μm. The filtrate was then heated and dried until the monochlorobenzene solvent reached 50 ppm, and hydrogenated nitrile rubber A was isolated. The iodine value, weight average molecular weight, and metal content of the obtained hydrogenated nitrile rubber A were measured. The results are shown in Table 1.
[0103] <Preparation of positive electrode binder> NMP was added to the hydrogenated nitrile rubber A described above to prepare 1 kg of a positive electrode binder having a solid content concentration of 8%. 920 parts of NMP was weighed out and placed in a 2 L container equipped with a stirring blade and heated to 80° C. Next, 80 parts of hydrogenated nitrile rubber A was added and dissolved while continuing to stir for 5 hours to prepare a positive electrode binder with a solid content concentration of 8%.
[0104] <Preparation of Conductive Dispersion Liquid> Multi-walled carbon nanotubes as conductive materials (BET specific surface area: 250 m 25 parts of 1000g / g, 12.5 parts of the positive electrode binder having a solid content concentration of 8% obtained as described above (corresponding to 1 part as solid content), and 82.5 parts of NMP as an organic solvent were added, and the mixture was stirred using a disper (3000 rpm, 10 minutes), and then mixed for 1 hour at a peripheral speed of 8 m / s using a bead mill (manufactured by Ashizawa Finetech, "LMZ015") using zirconia beads having a diameter of 1 mm, to prepare a conductive material dispersion, whose viscosity was measured and the results are shown in Table 1. The stability of the dispersion was also evaluated and the results are shown in Table 1.
[0105] <Preparation of slurry for secondary battery positive electrode> In the above-mentioned conductive material dispersion, a ternary active material having a layered structure (LiNi 0.5 Co 0.2 Mn 0.3 98.0 parts of 02) (average particle size: 10 μm), 1.0 part of polyvinylidene fluoride as a binder, 1.0 part of the conductive material dispersion (solid content equivalent), and NMP were added and mixed with a planetary mixer (60 rpm, 30 minutes) to prepare a positive electrode slurry. The amount of NMP added was adjusted so that the viscosity of the resulting positive electrode slurry (measured with a single cylindrical rotational viscometer in accordance with JIS Z8803:1991. Temperature: 25°C, rotation speed: 60 rpm) was within the range of 4000 to 5000 mPa·s.
[0106] <Preparation of positive electrode> An aluminum foil having a thickness of 20 μm was prepared as a current collector. The above-mentioned positive electrode slurry was applied to the aluminum foil with a comma coater so that the coating weight after drying was 20 mg / cm. 2 The coating was applied so that the coating would become 1.5 g / cm 2 , and the coating was dried at 120°C for 5 minutes and at 130°C for 5 minutes, and then heat-treated at 60°C for 10 hours to obtain a positive electrode blank. This positive electrode blank was rolled with a roll press to obtain a positive electrode blank with a density of 3.5 g / cm 2 . 3 A sheet-shaped positive electrode was prepared by combining the positive electrode mixture layer and aluminum foil. This sheet-shaped positive electrode was cut to a width of 4.8 cm and a length of 50 cm to prepare a positive electrode for a lithium ion secondary battery. The peel strength of the obtained positive electrode for a lithium ion secondary battery was evaluated, and the results are shown in Table 1.
[0107] <Preparation of negative electrodes for lithium-ion secondary batteries> In a 5MPa pressure vessel equipped with a stirrer, 33 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 3.5 parts of itaconic acid as a carboxylic acid group-containing monomer, 63.5 parts of styrene as an aromatic vinyl monomer, 0.4 parts of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of ion-exchanged water, and 0.5 parts of potassium persulfate as a polymerization initiator were added, thoroughly stirred, and then heated to 50°C to start polymerization. When the polymerization conversion rate reached 96%, the mixture was cooled to stop the polymerization reaction, and a mixture containing a particulate binder (styrene-butadiene copolymer) was obtained. After adjusting the pH to 8 by adding a 5% aqueous sodium hydroxide solution to the above mixture, the unreacted monomer was removed by heating and vacuum distillation. The mixture was then cooled to 30°C or less to obtain an aqueous dispersion containing a binder for the negative electrode.
[0108] Next, 48.75 parts of artificial graphite and 48.75 parts of natural graphite as negative electrode active materials, and 1 part of carboxymethyl cellulose as a thickener were added to a planetary mixer. The mixture was then diluted with ion-exchanged water to a solid content concentration of 60%, and then kneaded for 60 minutes at a rotation speed of 45 rpm. Then, 1.5 parts of the aqueous dispersion containing the negative electrode binder obtained as described above was added in terms of solid content, and kneaded for 40 minutes at a rotation speed of 40 rpm. Then, ion-exchanged water was added so that the viscosity became 3000±500 mPa·s (measured with a B-type viscometer at 25°C and 60 rpm), thereby preparing a slurry for the negative electrode mixture layer.
[0109] Next, a copper foil having a thickness of 15 μm was prepared as a current collector. The negative electrode slurry was applied to both sides of the copper foil in a coating amount of 10 mg / cm after drying. 2 The negative electrode blank was rolled by a roll press to a density of 1.6 g / cm. 3 A sheet-shaped negative electrode was produced consisting of the negative electrode mixture layer (on both sides) and copper foil. The sheet-shaped negative electrode was then cut to a width of 5.0 cm and a length of 52 cm to prepare a negative electrode for a lithium ion secondary battery.
[0110] <Production of lithium-ion secondary battery> The prepared positive electrode for lithium ion secondary battery and negative electrode for lithium ion secondary battery were arranged so that the electrode mixture layers faced each other, and a separator (microporous film made of polyethylene) having a thickness of 15 μm was interposed between them, and the electrodes were wound around a core having a diameter of 20 mm to obtain a wound body. The wound body obtained was then compressed in one direction at a speed of 10 mm / sec until the thickness became 4.5 mm. The wound body after compression had an elliptical shape in a plan view, and the ratio of the major axis to the minor axis (major axis / minor axis) was 7.7.
[0111] In addition, a 1.0 M LiPF6 solution (solvent: a mixed solvent of ethylene carbonate (EC) / diethyl carbonate (DEC) = 3 / 7 (volume ratio), additive: containing 2 volume % vinylene carbonate (solvent ratio)) was prepared as an electrolyte.
[0112] The compressed wound body was then housed in an aluminum laminate case together with 3.2 g of non-aqueous electrolyte. A nickel lead wire was then connected to a predetermined location of the negative electrode, and an aluminum lead wire was connected to a predetermined location of the positive electrode, and the opening of the case was then sealed by heat to obtain a lithium ion secondary battery. This lithium ion secondary battery was a pouch-shaped battery of a predetermined size capable of housing the wound body, and had a nominal capacity of 700 mAh.
[0113] The obtained lithium ion secondary battery was evaluated for output characteristics, cycle characteristics, and cracking of the electrode active material after cycles. The results are shown in Table 1.
[0114] Example 2 Except for changing the amount of activated carbon used in the purification step to 0.5 parts, the same procedure as in Example 1 was followed to obtain hydrogenated nitrile rubber B. Measurements and performance evaluations of hydrogenated nitrile rubber B were carried out, and the results are shown in Table 1.
[0115] Example 3 Except for changing the amount of activated carbon used in the purification step to 0.08 parts, the same procedure as in Example 1 was followed to obtain hydrogenated nitrile rubber C. Hydrogenated nitrile rubber C was measured and its performance was evaluated, and the results are shown in Table 1.
[0116] Example 4 Except for changing the amount of activated carbon used in the purification step to 0.07 parts, the same procedure as in Example 1 was followed to obtain hydrogenated nitrile rubber D. Hydrogenated nitrile rubber D was measured and its performance was evaluated, and the results are shown in Table 1.
[0117] Example 5 Except for changing the amount of activated carbon used in the purification step to 0.05 parts, the same procedure as in Example 1 was followed to obtain hydrogenated nitrile rubber E. Hydrogenated nitrile rubber E was measured and its performance was evaluated, and the results are shown in Table 1.
[0118] Example 6 Except for changing the amount of activated carbon used in the purification step to 0.02 parts, the same procedure as in Example 1 was followed to obtain hydrogenated nitrile rubber F. Hydrogenated nitrile rubber F was measured and its performance was evaluated, and the results are shown in Table 1.
[0119] Example 7 Except for changing the amount of Grubbs catalyst in the metathesis reaction to 3000 ppm, hydrogenated nitrile rubber G was obtained in the same manner as in Example 1. Hydrogenated nitrile rubber G was measured and its performance was evaluated, and the results are shown in Table 1.
[0120] (Reference example 1) In the hydrogenation step II, 1 L of a monochlorobenzene solution containing Wilkinson's catalyst and triphenylphosphine was not added to the reactor, but 1000 ppm of palladium-silica (Pd / SiO2) was placed in the autoclave as a catalyst, and hydrogenation reaction was carried out under conditions of a temperature of 90°C and a hydrogen pressure of 3.0 MPa. In the purification step, in addition to the activated carbon, 1 part of aminopropyl group-modified silica (product name "QuadraSil AP", SIGMA-ALDRICH, silica with aminopropyl groups introduced on the surface, average particle size 54 μm) was added, and hydrogenated nitrile rubber H was obtained in the same manner as in Example 1. Measurements and performance evaluations of hydrogenated nitrile rubber H were carried out, and the results are shown in Table 1.
[0121] Comparative Example 1 Except for not adding an antioxidant, the procedure of Example 1 was repeated to obtain hydrogenated nitrile rubber I. Hydrogenated nitrile rubber I was measured and its performance was evaluated, and the results are shown in Table 1.
[0122] Comparative Example 2 Except for not adding an antioxidant, hydrogenated nitrile rubber J was obtained in the same manner as in Reference Example 1. Hydrogenated nitrile rubber J was measured and its performance was evaluated, and the results are shown in Table 1.
[0123] [Table 1]
[0124] From Table 1, it can be seen that the hydrogenated nitrile rubbers A to G obtained by the production method of the present invention are excellent in the viscosity characteristics (dispersibility) and stability of the conductive material dispersion, increase the peel strength of the produced electrodes, and are also excellent in the output characteristics and cycle characteristics of the electrochemical element and the effect of suppressing cracking of the electrode active material after the cycle test, and each characteristic is highly balanced (comparison between Examples 1 to 7 and Comparative Examples 1 and 2).
[0125] It is found that the viscosity characteristics (dispersibility) of the conductive material dispersion are affected by the Ca content in the hydrogenated nitrile rubber produced, and as the Ca content increases, the dispersion viscosity increases and deteriorates slightly (Examples 5 and 6). Therefore, it is found that the viscosity characteristics of the conductive material dispersion are excellent when the Ca content in the hydrogenated nitrile rubber produced is small.
[0126] It is understood that the stability of the conductive material dispersion liquid deteriorates if the hydrogenated nitrile rubber produced does not contain a phenol-based antioxidant (BHT) (Comparative Examples 1-2). Therefore, it is understood that in order to improve the stability of the conductive material dispersion liquid, it is important that the phenol-based antioxidant added during the production process remains in the hydrogenated nitrile rubber produced. In the production method of the present invention, the added phenol-based antioxidant was incorporated into the hydrogenated nitrile rubber almost as it was, which was preferable.
[0127] It is found that the peel strength of the electrode tends to deteriorate when the Ca content in the hydrogenated nitrile rubber produced is low (Example 2), and also tends to deteriorate when the iodine content is low (Example 7). Therefore, in order to increase the peel strength of the electrode, it is important to increase the Ca content in the hydrogenated nitrile rubber produced and to increase the iodine value.
[0128] The output characteristics of the electrochemical element were good for all of the hydrogenated nitrile rubbers A to J produced.
[0129] It is found that the cycle characteristics of the electrochemical element are greatly affected by the amount of Ca in the hydrogenated nitrile polymer produced, and tend to deteriorate when the amount is too large (comparison among Examples 1 to 6). Therefore, in order to improve the cycle characteristics, it is preferable to limit the Ca content in the hydrogenated nitrile rubber produced to a small amount.
[0130] The cracking of the electrode active material after the cycle test of the electrochemical element tends to worsen when the amount of Ca in the hydrogenated nitrile rubber produced is small (comparison between Examples 1 to 6). It is also found that the cracking worsens when an excessive amount of Pd, which is a catalyst component, remains (Reference Example 1 and Comparative Example 2). Therefore, in order to improve the cycle characteristics of the electrochemical element, it is preferable to increase the amount of Ca in the hydrogenated nitrile rubber produced and not leave hydrogenation catalyst residues such as Pd.
[0131] On the other hand, although not shown in this comparative example, if the hydrogenated nitrile rubber produced contains excessive amounts of Ru, Rh, Mg and Na, the cycle characteristics of the electrochemical element are poor and the electrode active material cracks after the cycle test. However, from Table 1, it can be seen that the range of metal contents in the hydrogenated nitrile rubbers A to G produced according to the present invention does not affect the cycle characteristics or the electrode active material cracking.
[0132] From Table 1, it can be seen that it is difficult to balance these six properties, since each performance evaluation is greatly influenced by the magnitude of the properties of the hydrogenated nitrile rubber produced or by slight differences in the metal content, and many of them give conflicting results. Among them, it can be seen that those using hydrogenated nitrile rubbers A to G produced by the production method of the present invention have a high degree of balance of these properties and are preferable. In particular, hydrogenated nitrile rubbers C and D were rated A in all evaluation items, and it can be seen that the electrochemical element properties are optimal when the amount of Ca in the hydrogenated nitrile rubber is within a specific range. [Industrial Applicability]
[0133] According to the present invention, there can be provided a method for producing hydrogenated nitrile rubber which provides a conductive material dispersion with excellent viscosity characteristics and stability, increases the peel strength of an electrode, prevents cracking of an active material, and improves the cycle characteristics and output characteristics of an electrochemical element.
Claims
1. A method for producing hydrogenated nitrile rubber, comprising emulsion polymerizing a monomer component containing a nitrile group-containing monomer and a conjugated diene monomer, adding a phenol-based antioxidant, coagulating the polymer with calcium chloride, and hydrogenating the polymer with a rhodium-based catalyst and / or a ruthenium-based catalyst.
2. The method for producing hydrogenated nitrile rubber according to claim 1, further comprising a step of purifying the hydrogenated nitrile rubber after the hydrogenation.
3. The method for producing hydrogenated nitrile rubber according to claim 1, wherein the hydrogenated nitrile rubber contains a phenol-based antioxidant, has an iodine value of 150 mg / 100 mg or less, a calcium (Ca) amount of 4000 ppm or less, a rhodium (Rh) and / or ruthenium (Ru) content of 50 ppm or less, a sodium (Na) content of 300 ppm or less, a magnesium (Mg) content of 50 ppm or less, and a palladium (Pd) content of 50 ppm or less.
4. The method for producing hydrogenated nitrile rubber according to claim 3, wherein the hydrogenated nitrile rubber is used as a binder for a positive electrode of an electrochemical element.
Citation Information
Patent Citations
Phenol-containing hydrogenated nitrile rubber
JP2018145434A
Binder composition for nonaqueous secondary battery positive electrode, composition for nonaqueous secondary battery positive electrode, positive electrode for nonaqueous secondary battery, and nonaqueous secondary battery
JP2018160421A
Dispersant composition for electrochemical elements, conductive material dispersion for electrochemical elements, slurry composition for electrochemical element electrodes and method for producing the same, electrodes for electrochemical elements, and electrochemical elements
JP6911985B1
Nonaqueous secondary battery
WO2022163769A1